The Vasarhelyi Method of Child Art Psychotherapy: An Adjunctive Treatment in Childhood Depression - Coşkunlu, Aynur; Tanıl, Ezgi; Coffey, Anne; Büyüktaşkın, Dicle; Mulligan, Aisling (Taylor and Francis Group, 2018)
We describe the use of child art psychotherapy (CAP) following the Vasarhelyi method in an 11-year-old female with a history of anxiety and depression which limited her capacity to attend school and in a 15-year-old male who had a history of depressive symptoms with suicidal thinking. In each case, the use of other therapies such as cognitive behaviour therapy was not possible or unsuccessful. Through the creation of images, each young person revealed concerns which had not been previously verbalised, and recovery was linked in time to the revelation of these worries. We propose the use of the Vasarhelyi method of CAP as an adjunctive treatment of depression in young people.